The effect of a digital health coaching and health education protocol on cognition in adults at-risk for Alzheimer’s - Anthony Campitelli; Joshua L. Gills; Megan D. Jones; Sally Paulson; Jennifer Myers; Kelsey Bryk; Erica N. Madero; Jordan M. Glenn; Charlie H. Rodgers; Jenova A. Kempkes; Michelle Gray (GeroScience, 2023)
Several modifiable lifestyle factors have been linked to cognitive ability and the risk of developing Alzheimer’s disease and related dementias (ADRD). Health coaching (HC) is an intervention that addresses lifestyle factors associated with cognition. The effectiveness of an HC protocol was evaluated and compared with a health education (HE) intervention, representing the current standard of care, in a sample of 216 adults between the ages of 45 and 75 years who were at-risk for developing ADRD. Outcomes examined were global cognition, neuropsychological cognition, and Alzheimer’s risk. HC participants received personalized coaching from a health coach focusing on nutrition, physical activity, sleep, stress, social engagement, and cognitive activity. HE participants received biweekly education materials focusing on the same modifiable lifestyle factors addressed by HC. Participants were assessed at baseline and again 4 months later. Self-reported global cognition scores improved only in the HC group (16.18 to 15.52, p = .03) and neuropsychological cognitive ability improved in the HE group (104.48 to 108.76, p < .001). When non-adherence in the HC group was accounted for, however, the mean change in neuropsychological score was similar between groups ( p > .05), self-reported global cognition demonstrated an even larger mean improvement in the HC group (16.20 to 15.41, p = .01), and the HC group saw an improvement in ADRD protective risk score (− 10.39 to − 11.45, p = .007). These results indicate that HC and HE can both improve cognition, but HC may be more effective and may yield increased protection against ADRD risk.

The Society for Environmental Geochemistry and Health (SEGH): building for the future of early career researchers - O. S. Humphrey; D. R. S. Middleton; S. Ahmad; T. Cocerva; S. M. Dowell; R. Garza-Galndo; E. M. Hamilton; N. Kafwamfwa; B. Kaninga; P. Kourgia; I. S. Ligowe; H. A. MacLeod; et al. (Environmental Geochemistry and Health, 2021)

Conspecific brood parasitism in an upland-nesting bird: cues parasites use to select a nest - Natalie J. Thimot; Rodger D. Titman; Kyle H. Elliott; Shawn R. Craik (Behavioral Ecology and Sociobiology, 2020)

Costs and response to conspecific brood parasitism by colonial red-breasted mergansers - Shawn R. Craik; Rodger D. Titman; Jean-Pierre L. Savard; Mohammadi Kaouass; Natalie Thimot; Kyle H. Elliott; Éric Tremblay (Journal of Ethology, 2018)

Investigation of co‐infections with pathogens associated with gill disease in Atlantic salmon during an amoebic gill disease outbreak - J K Downes; T Yatabe; M Marcos‐Lopez; H D Rodger; E MacCarthy; I O'Connor; E Collins; N M Ruane (Journal of Fish Diseases, 2018)
Gill diseases are a complex and multifactorial challenge for marine farmed Atlantic salmon. Co‐infections with putative pathogens are common on farms; however, there is a lack of knowledge in relation to the potential effect co‐infections may have on pathology. The objective of this study was to determine the prevalence and potential effects of Neoparamoeba perurans, Desmozoon lepeophtherii , Candidatus Branchiomonas cysticola, Tenacibaculum maritimum and salmon gill poxvirus ( SGPV ) during a longitudinal study on a marine Atlantic salmon farm. Real‐time PCR was used to determine the presence and sequential infection patterns of these pathogens on gill samples collected from stocking until harvest. A number of multilevel models were used to determine the effect of these putative pathogens on gill health (measured as gill histopathology score), while adjusting for the effect of water temperature and time since the last freshwater treatment. Results indicate that between 12 and 16 weeks post‐seawater transfer (wpst), colonization of the gills by all pathogens had commenced and by week 16 of marine production each of the pathogens had been detected. D. lepeophtherii and Candidatus B. cysticola were by far the most prevalent of the potential pathogens detected during this study. Detections of T. maritimum were found to be significantly correlated with temperature showing distinct seasonality. Salmon gill poxvirus was found to be highly sporadic and detected in the first sampling point, suggesting a carryover from the freshwater stage of production. Finally, the model results indicated no clear effect between any of the pathogens. Additionally, the models showed that the only variable which had a consistent effect on the histology score was N. perurans .

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

Solar Photocatalysis Using Fixed-Film TiO2 for Microcystins from Colonial Microcystis aeruginosa - Ciera M. Kinley; Maas Hendrikse; Alyssa J. Calomeni; Tyler D. Geer; John H. Rodgers (Water, Air, & Soil Pollution, 2018)

Relationship among aqueous copper half-lives and responses of Pimephales promelas to a series of copper sulfate pentahydrate concentrations - Alyssa J. Calomeni; Ciera M. Kinley; Tyler D. Geer; Kyla J. Iwinski; Maas Hendrikse; John H. Rodgers (Ecotoxicology, 2018)

Microcystin-LR Degradation Following Copper-Based Algaecide Exposures - Ciera M. Kinley; Kyla J. Iwinski-Wood; Tyler D. Geer; Maas Hendrikse; Andrew D. McQueen; Alyssa J. Calomeni; Jenny Liang; Vanessa Friesen; Monique C. Simair; John H. Rodgers (Water, Air, & Soil Pollution, 2018)

Oxidative stress is associated with late‐stage amoebic gill disease in farmed Atlantic salmon ( Salmo salar L.) - M Marcos‐López; C Ruiz Espinosa; H D Rodger; I O'Connor; E MacCarthy; M A Esteban (Journal of Fish Diseases, 2018)

Piscine myocarditis virus detected in corkwing wrasse ( Symphodus melops ) and ballan wrasse ( Labrus bergylta ) - F Scholz; N M Ruane; T Morrissey; M Marcos‐López; S Mitchell; I O'Connor; L Mirimin; E MacCarthy; H D Rodger (Journal of Fish Diseases, 2018)

Characterization of Copper Algaecide (Copper Ethanolamine) Dissipation Rates Following Pulse Exposures - Alyssa J. Calomeni; Kyla J. Iwinski; Andrew D. McQueen; Ciera M. Kinley; Maas Hendrikse; John H. Rodgers (Water, Air, & Soil Pollution, 2017)

Piscirickettsia salmonis infection in cultured lumpfish ( Cyclopterus lumpus L.) - M Marcos‐López; N M Ruane; F Scholz; M Bolton‐Warberg; S O Mitchell; S Murphy O'Sullivan; A Irwin Moore; H D Rodger (Journal of Fish Diseases, 2017)
A Piscirickettsia salmonis infection was diagnosed in lumpfish ( Cyclopterus lumpus L.) juveniles held in a marine research facility on the west coast of Ireland. The main clinical signs and pathology included marked ascites, severe multifocal liver necrosis and severe diffuse inflammation and necrosis of the exocrine pancreas and peri‐pancreatic adipose tissue. Numerous Piscirickettsia ‐like organisms were observed by histopathology in the affected organs, and the bacterial species was characterized by molecular analysis. Sequencing of the partial 16S rDNA gene and internal transcribed spacer region showed the lumpfish sequences to be closely related to previously identified Atlantic salmon ( Salmo salar L.) sequences from Ireland. To the authors’ knowledge, this is the first detection of P. salmonis in lumpfish worldwide. The infection is considered potentially significant in terms of lumpfish health and biosecurity.

First record of Tetramicra brevifilum in lumpfish ( Cyclopterus lumpus, L.) - F Scholz; E Fringuelli; M Bolton‐Warberg; M Marcos‐López; S Mitchell; P Prodhol; D Moffet; P Savage; S Murphy O'Sullivan; I O′Connor; E McCarthy; H D Rodger (Journal of Fish Diseases, 2017)
A microsporidian species with 98.3–98.4% nucleotide identity to Tetramicra brevifilum ( Journal of Fish Diseases , 3 , 1980, 495) was diagnosed in lumpfish ( Cyclopterus lumpus , L.) broodstock held at a breeding and rearing facility in western Ireland. The fish were wild‐caught from the west coast of Ireland, and the first case was diagnosed one year after capture. Clinical signs included severe bloating, lethargy, exophthalmos, anorexia, white patches on the cornea and externally visible parasitic cysts on skin and fins. Necropsy revealed severe ascites, white nodules and vacuoles in all the internal organs and partial liquefaction of the skeletal muscle. On histological examination, microsporidian xenomas were observed in all internal organs, the skin, skeletal muscle, gills and the eyes. The microsporidian species was identified by molecular analysis and transmission electron microscopy. This is the first record of T. brevifilum infecting lumpfish, and the disease is considered to be of potential significance to the rising aquaculture industry of this species.

Predicting In Situ Responses of Taste- and Odor-Producing Algae in a Southeastern US Reservoir to a Sodium Carbonate Peroxyhydrate Algaecide Using a Laboratory Exposure-Response Model - Tyler D. Geer; Alyssa J. Calomeni; Ciera M. Kinley; Kyla J. Iwinski; John H. Rodgers (Water, Air, & Soil Pollution, 2017)

Technical pre‐analytical effects on the clinical biochemistry of Atlantic salmon ( Salmo salar L.) - M Braceland; K Houston; A Ashby; C Matthews; H Haining; H Rodger; P D Eckersall (Journal of Fish Diseases, 2017)
Clinical biochemistry has long been utilized in human and veterinary medicine as a vital diagnostic tool, but despite occasional studies showing its usefulness in monitoring health status in Atlantic salmon ( Salmo salar L.), it has not yet been widely utilized within the aquaculture industry. This is due, in part, to a lack of an agreed protocol for collection and processing of blood prior to analysis. Moreover, while the analytical phase of clinical biochemistry is well controlled, there is a growing understanding that technical pre‐analytical variables can influence analyte concentrations or activities. In addition, post‐analytical interpretation of treatment effects is variable in the literature, thus making the true effect of sample treatment hard to evaluate. Therefore, a number of pre‐analytical treatments have been investigated to examine their effect on analyte concentrations and activities. In addition, reference ranges for salmon plasma biochemical analytes have been established to inform veterinary practitioners and the aquaculture industry of the importance of clinical biochemistry in health and disease monitoring. Furthermore, a standardized protocol for blood collection has been proposed.

The epidemiology of pancreas disease in salmonid aquaculture: a summary of the current state of knowledge - M D Jansen; B Bang Jensen; M F McLoughlin; H D Rodger; T Taksdal; H Sindre; D A Graham; A Lillehaug (Journal of Fish Diseases, 2017)
Pancreas disease ( PD ) is a viral disease caused by Salmonid alphavirus ( SAV ) that affects farmed Atlantic salmon ( Salmo salar L.) and rainbow trout ( Oncorhynchus mykiss (Walbaum)) in the seawater phase. Since its first description in Scotland in 1976, a large number of studies have been conducted relating to the disease itself and to factors contributing to agent spread and disease occurrence. This paper summarizes the currently available, scientific information on the epidemiology of PD and its associated mitigation and control measures. Available literature shows infected farmed salmonids to be the main reservoir of SAV . Transmission between seawater sites occurs mainly passively by water currents or actively through human activity coupled with inadequate biosecurity measures. All available information suggests that the current fallowing procedures are adequate to prevent agent survival within the environment through the fallowing period and thus that a repeated disease outbreak at the same site is due to a new agent introduction. There has been no scientific evaluation of currently used on‐site biosecurity measures, and there is limited information on the impact of available mitigation measures and control strategies.

Effects of Acid Volatile Sulfides (AVS) from Na2S-Amended Sediment on Hyalella azteca - Andrew D. McQueen; Ciera M. Kinley; Kyla J. Iwinski; Alyssa J. Calomeni; John H. Rodgers (Water, Air, & Soil Pollution, 2016)

Photocatalysis of a Commercial Naphthenic Acid in Water Using Fixed-Film TiO2 - Andrew D. McQueen; Ciera M. Kinley; Rebecca L. Kiekhaefer; Alyssa J. Calomeni; John H. Rodgers; James W. Castle (Water, Air, & Soil Pollution, 2016)

Sediment Copper Concentrations, In Situ Benthic Invertebrate Abundance, and Sediment Toxicity: Comparison of Treated and Untreated Coves in a Southern Reservoir - Kyla J. Iwinski; Andrew D. McQueen; Ciera M. Kinley; Alyssa J. Calomeni; Tyler D. Geer; John H. Rodgers (Water, Air, & Soil Pollution, 2016)

Pathology and mortality associated with the mauve stinger jellyfish P elagia noctiluca in farmed A tlantic salmon S almo salar L. - M Marcos‐López; S O Mitchell; H D Rodger (Journal of Fish Diseases, 2016)

Genomic comparison of virulent and non‐virulent S treptococcus agalactiae in fish - C M J Delannoy; R N Zadoks; M Crumlish; D Rodgers; F A Lainson; H W Ferguson; J Turnbull; M C Fontaine (Journal of Fish Diseases, 2016)
Streptococcus agalactiae infections in fish are predominantly caused by beta‐haemolytic strains of clonal complex ( CC ) 7, notably its namesake sequence type ( ST ) 7, or by non‐haemolytic strains of CC 552, including the globally distributed ST 260. In contrast, CC 23, including its namesake ST 23, has been associated with a wide homeothermic and poikilothermic host range, but never with fish. The aim of this study was to determine whether ST 23 is virulent in fish and to identify genomic markers of fish adaptation of S . agalactiae . Intraperitoneal challenge of Nile tilapia, O reochromis niloticus ( L innaeus), showed that ST 260 is lethal at doses down to 10 2 cfu per fish, whereas ST 23 does not cause disease at 10 7 cfu per fish. Comparison of the genome sequence of ST 260 and ST 23 with those of strains derived from fish, cattle and humans revealed the presence of genomic elements that are unique to subpopulations of S . agalactiae that have the ability to infect fish ( CC 7 and CC 552). These loci occurred in clusters exhibiting typical signatures of mobile genetic elements. PCR ‐based screening of a collection of isolates from multiple host species confirmed the association of selected genes with fish‐derived strains. Several fish‐associated genes encode proteins that potentially provide fitness in the aquatic environment.

Analysis of Algaecide Exposures: an Evaluation of the I3 − Method to Measure Sodium Carbonate Peroxyhydrate Algaecides - Ciera M. Kinley; John H. Rodgers; Kyla J. Iwinski; Andrew D. McQueen; Alyssa J. Calomeni (Water, Air, & Soil Pollution, 2015)

An outbreak of francisellosis in wild‐caught C eltic S ea A tlantic cod, G adus morhua L., juveniles reared in captivity - N M Ruane; M Bolton‐Warberg; H D Rodger; D J Colquhoun; M Geary; S J McCleary; K O'Halloran; K Maher; D O'Keeffe; L Mirimin; K Henshilwood; F Geoghegan; et al. (Journal of Fish Diseases, 2015)

Clinical cardiomyopathy syndrome in Atlantic salmon, Salmo salar L. - H D Rodger; S J McCleary; N M Ruane (Journal of Fish Diseases, 2014)

Differential characterization of emerging skin diseases of rainbow trout – a standardized approach to capturing disease characteristics and development of case definitions - B Oidtmann; S E LaPatra; D Verner‐Jeffreys; M Pond; E J Peeler; P A Noguera; D W Bruno; S St‐Hilaire; C B Schubiger; K Snekvik; M Crumlish; D M Green; et al. (Journal of Fish Diseases, 2013)
Farmed and wild salmonids are affected by a variety of skin conditions, some of which have significant economic and welfare implications. In many cases, the causes are not well understood, and one example is cold water strawberry disease of rainbow trout, also called red mark syndrome, which has been recorded in the UK since 2003. To date, there are no internationally agreed methods for describing these conditions, which has caused confusion for farmers and health professionals, who are often unclear as to whether they are dealing with a new or a previously described condition. This has resulted, inevitably, in delays to both accurate diagnosis and effective treatment regimes. Here, we provide a standardized methodology for the description of skin conditions of rainbow trout of uncertain aetiology. We demonstrate how the approach can be used to develop case definitions, using coldwater strawberry disease as an example.

Geographical distribution of salmonid alphavirus subtypes in marine farmed Atlantic salmon, Salmo salar L., in Scotland and Ireland - D A Graham; E Fringuelli; H M Rowley; D Cockerill; D I Cox; T Turnbull; H Rodger; D Morris; M F Mc Loughlin (Journal of Fish Diseases, 2012)
Sequence data from salmonid alphavirus (SAV) strains obtained from farmed marine Atlantic salmon, Salmo salar L. , over a 20‐year period between 1991 and 2011 was reviewed to examine the geographical distribution of the genetically defined SAV subtypes in twelve regions across Ireland and Scotland. Of 160 different Atlantic salmon SAV strains examined, 62 belonged to subtype 1, 28 to subtype 2, 34 to subtype 4, 35 to subtype 5 and 1 to subtype 6. SAV subtypes 1, 4 and 6 were found in Ireland, while subtypes 1, 2, 4 and 5 were found in Scotland. In the majority of regions, there was a clear clustering of subtypes, with SAV subtype 1 being the dominant subtype in Ireland overall, as well as in Argyll and Bute in Scotland. SAV subtype 2 predominated in the Shetland and Orkney Islands. The emergence in Atlantic salmon of subtype 2 strains typically associated with sleeping disease in rainbow trout in Argyll and Bute, strongly suggesting transmission of infection between these species, was noted for the first time. SAV subtype 4 was the most common subtype found in the southern Western Isles, while SAV subtype 5 predominated in the northern Western Isles and north‐west mainland Scotland. No single strain was dominant on sites in the western Highlands, with a number of sites in this region in particular having more than one subtype detected in different submissions. The significance of these results in relation to aspects of the epidemiology of infection, including transmission, biosecurity and wildlife reservoirs are discussed and knowledge gaps identified.

Detection of Neoparamoeba perurans by duplex quantitative Taqman real‐time PCR in formalin‐fixed, paraffin‐embedded Atlantic salmonid gill tissues - E Fringuelli; A W Gordon; H Rodger; M D Welsh; D A Graham (Journal of Fish Diseases, 2012)
The development and the application of a quantitative duplex real‐time PCR for the detection of Neoparamoeba perurans and the elongation factor α 1 gene (ELF) of Atlantic salmon, Salmo salar L., and rainbow trout, Oncorhynchus mykiss (Walbaum), are described. A set of primers and probe was designed to amplify a 139‐bp fragment specific to the N. perurans 18S rRNA gene. The test was shown to be very sensitive, being able to detect as little as 13.4 DNA copies per μL corresponding to 0.15 fg of template DNA. In addition, the reaction that detected N. perurans was found to have a high degree of repeatability and reproducibility, to have a linear dynamic range ( R 2 = 0.999) extending over 5 log 10 dilutions and to have a high efficiency (104%). The assay was applied to DNA samples extracted from 48 formalin‐fixed, paraffin‐embedded (FFPE) salmon gill tissues showing varying degrees of gill histopathology and amoebic gill disease (AGD)‐type histopathology ranging from absent to severe (each scored 0–3). Neoparamoeba perurans DNA was detected in all the blocks where AGD‐type histopathology was diagnosed microscopically and in 43.6% of the blocks showing signs of gill pathology. The association between parasitic load and gill histopathology and AGD‐type histopathology severity was also investigated. This study also describes the development and the application of a second real‐time PCR for the generic detection of Neoparamoeba spp ., Page, 1987. A set of primers and probe conserved among the Neoparamoeba spp. was designed to amplify a 150‐bp fragment within the 18S rRNA gene. Applied to N. perurans‐ negative gill tissues, the method was used to exclude the presence of other Neoparamoeba spp. in those blocks where gill pathology was observed microscopically.

Development of a quantitative real‐time PCR for the detection of Tenacibaculum maritimum and its application to field samples - E Fringuelli; P D Savage; A Gordon; E J Baxter; H D Rodger; D A Graham (Journal of Fish Diseases, 2012)
The development and the application of a quantitative real‐time PCR for the detection of Tenacibaculum maritimum are described. A set of primers and probe was designed to amplify a 155‐bp fragment specific to the T. maritimum 16S rRNA gene. The test was shown to be very sensitive, able to detect as little as 4.8 DNA copies number μL −1 . In addition, the assay was found to have a high degree of repeatability and reproducibility, with a linear dynamic range ( R 2 = 0.999) extending over 6 log 10 dilutions and a high efficiency (100%). The assay was applied to DNA samples extracted from 48 formalin‐fixed paraffin‐embedded (FFPE) Atlantic salmon, Salmo salar, gill tissues showing varying degrees of gill pathology (scored 0–3) and from 26 jellyfish samples belonging to the species Phialella quadrata and Muggiaea atlantica . For each sample, the bacterial load was normalised against the level of the salmonid elongation factor alpha 1 (ELF) detected by a second real‐time PCR using previously published primers and probe. Tenacibaculum maritimum DNA was detected in 89% of the blocks with no signs of gill disease as well as in 95% of the blocks with mild‐to‐severe gill pathology. Association between bacterial load and gill pathology severity was investigated. T. maritimum DNA was detected at low level in four of the 26 jellyfish tested.

Epitheliocystis in Atlantic salmon, Salmo salar L., farmed in fresh water in Ireland is associated with ‘ Candidatus Clavochlamydia salmonicola’ infection - S O Mitchell; T Steinum; H Rodger; C Holland; K Falk; D J Colquhoun (Journal of Fish Diseases, 2010)
Intracellular inclusions containing chlamydia‐like organisms are frequently observed in the gill epithelial cells of Atlantic salmon, Salmo salar L., cultured in fresh water in Ireland. In this study, the causative agent was identified in four separate freshwater sites, using 16s rRNA sequencing, as ‘ Candidatus Clavochlamydia salmonicola’. Histopathology and real‐time (RT) PCR were used to further assess infections. The prevalence of infection ranged from 75–100% between sites and infection intensity was highly variable. No significant lesions were associated with these infections. As a diagnostic tool, RT‐PCR proved marginally more sensitive than histopathology. The fate of ‘ Candidatus Clavochlamydia salmonicola’ in Atlantic salmon post‐seawater transfer was investigated in a 12‐week marine longitudinal study. Both RT‐PCR and histopathological examination indicate that the organism disappears from the gills 4–6 weeks post‐transfer.

Prospective longitudinal studies of salmonid alphavirus infections on two Atlantic salmon farms in Ireland; evidence for viral persistence - D A Graham; E Fringuelli; C Wilson; H M Rowley; A Brown; H Rodger; M F McLoughlin; C McManus; E Casey; L J McCarthy; N M Ruane (Journal of Fish Diseases, 2010)
Prospective longitudinal studies of two outbreaks of pancreas disease in Atlantic salmon (AS), Salmo salar L., in Ireland were conducted. Both outbreaks occurred during the marine phase of production, with one caused by salmonid alphavirus subtype 1 (SAV1) and the other by SAV4. In addition to screening a range of tissues by real‐time reverse transcriptase polymerase chain reaction (RRT‐PCR), virological, serological and histopathological examinations were performed along with partial genome sequencing and results were related to environmental and production data and farm history. On Farm 1 (marine sampling only), infection was detected within 3 weeks of smolts being placed on the farm, while on Farm 2 (freshwater and marine sampling), infection was first detected 315 days after transfer to sea. In both outbreaks, RRT‐PCR signals were detected in a range of tissues including gill, heart, kidney, pancreas/pyloric caeca, brain and serum. Persistence of signal was longest in gill and heart (≥265 days on both farms) and shortest in serum. Mortalities on the two farms varied from 10.9% to 30%. In both cases, partial genome sequence of the causative viruses were identical to SAV strains detected in previous populations of AS on each of the study farms, including populations with which the study populations overlapped in time and space.

Phylogenetic analyses and molecular epidemiology of European salmonid alphaviruses (SAV) based on partial E2 and nsP3 gene nucleotide sequences - E Fringuelli; H M Rowley; J C Wilson; R Hunter; H Rodger; D A Graham (Journal of Fish Diseases, 2008)
Sequence data were generated for portions of the E2 and nsP3 genes of 48 salmonid alphaviruses from farmed Atlantic salmon (AS), Salmo salar L . , and rainbow trout (RT), Oncorhynchus mykiss (Walbaum), in marine and freshwater environments, respectively, from the Republic of Ireland, Northern Ireland, England, Scotland, Norway, France, Italy and Spain between 1991 and 2007. Based on these sequences, and those of six previously published reference strains, phylogenetic trees were constructed using the parsimony method. Trees generated with both gene segments were similar. Clades corresponding to the three previously recognized subtypes were generated and in addition, two further new clades of viruses were identified. A single further strain (F96‐1045) was found to be distinct from all of the other strains in the study. The percentage of nucleotide divergence within clades was generally low (0–4.8% for E2, 0–6.6% for nsP3). Interclade divergence tended to be higher (3.4–19.7% for E2, 6.5–28.1% for nsP3). Based on these results and using current SAV terminology, the two new clades and F96‐1045 were termed SAV subtypes 4, 5 and 6, respectively. SAV4 contained AS strains from Ireland and Scotland, while SAV5 contained only Scottish AS strains. Recently identified SAV strains from RT in Italy and Spain were shown to belong to SAV2. In addition, marine AS strains belonging to SAV2 were identified for the first time. Analysis of the origin of several clusters of strains with identical E2 and nsP3 sequences strongly support horizontal transmission of virus between farms and aquaculture companies. Evidence in support of vertical transmission was not found.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Erythrocytic inclusion body syndrome virus in wild Atlantic salmon, Salmo salar L. - H D Rodger (Journal of Fish Diseases, 2007)
An investigation was undertaken to establish aspects of the epizootiology of erythrocytic inclusion bodies in wild Atlantic salmon, Salmo salar L., in Scotland. From 1992 to 1995, adult and juvenile salmon, from Scottish rivers, were screened for the presence of erythrocytic inclusion bodies and haematological parameters measured. The nature of the inclusion bodies was assessed through transmission electron microscopy, negative‐staining and blood smear‐staining techniques and was demonstrated to be viral in origin with characteristics similar to a member of the family Togaviridae. Specifically, these were a viral genome of single‐stranded RNA, spherical virion morphology with an icosahedral core, average size of 70 nm and a buoyant density of 1.15–1.20 g cm −3 . The cytoplasmic inclusions were either large, single inclusions (1–2 μm) or smaller multiple inclusions (0.5–1 μm). A total of 4.2% ( n = 48) and 27.7% ( n = 213) of the parr and adult salmon, respectively, were positive for the presence of the inclusions. The intensity of the inclusions, when present, varied from light in parr to moderate and heavy in adults, when graded according to the number of inclusions per field of view. Neither haematological variations nor clinical disease was associated with the presence or absence of viral inclusions.

Longitudinal serological surveys of Atlantic salmon, Salmo salar L., using a rapid immunoperoxidase‐based neutralization assay for salmonid alphavirus - D A Graham; V A Jewhurst; H M Rowley; M F McLoughlin; H Rodger; D Todd (Journal of Fish Diseases, 2005)
Longitudinal serological surveys for salmon pancreas disease virus (SPDV), the causal agent of pancreas disease (PD), were conducted on multiple caged populations of Atlantic salmon, Salmo salar L., on two farms over a 77‐week period (farm 1, freshwater and marine stages) and a 36‐week period (farm 2, marine stage only), using a microtitre‐based virus neutralization (VN) assay. Collected sera were also screened for viraemia with SPDV, and pancreas, heart and muscle tissues were examined for lesions consistent with PD. Outbreaks of PD occurred during the marine phase on both farms, as demonstrated by seroconversion, the isolation of virus and progressive histopathological changes consistent with a PD outbreak. All populations monitored showed a progressive increase in seroprevalence of 90–100%, typically accompanied by rises in geometric mean antibody titres. With the exception of one caged population, which showed a marked biphasic seroprevalence pattern, the seroprevalence figures in the remaining four monitored populations remained high (≥70%) until the end of the study period. Peak VN titres of ≥1/1280 were detected on both farms. The results provide essential baseline information for the interpretation of SPDV VN serology results, and indicate that this methodology is suited to both the diagnosis and seroepidemiology of SPDV infections.

The Responses of Selected Terrestrial Plants to Short (<12 days) and Long Term (2, 4 and 6 Weeks) Hexahydro-1,3,5-Trinitro-1,3,5-Triazine (RDX) Exposure. Part I: Growth and Developmental Effects - Linda E. Winfield; John H. Rodger; Stephen J. D'surney (Ecotoxicology, 2004)

Effects of a Homologous Series of Linear Alcohol Ethoxylate Surfactants on Fathead Minnow Early Life Stages - R. E. Lizotte Jr.; D. C. L. Wong; P. B. Dorn; J. H. Rodgers Jr. (Archives of Environmental Contamination and Toxicology, 1999)

Copper Bioavailability in Steilacoom Lake Sediments - D. B. Huggett; W. B. Gillespie Jr.; J. H. Rodgers Jr. (Archives of Environmental Contamination and Toxicology, 1999)

Comparative Toxicity of Chlordane, Chlorpyrifos, and Aldicarb to Four Aquatic Testing Organisms - M. T. Moore; D. B. Huggett; W. B. Gillespie Jr.; J. H. Rodgers Jr.; C. M. Cooper (Archives of Environmental Contamination and Toxicology, 1998)